Model of Entrepreneurship Learning in Growing New Entrepreneur (Case Study in Centre of Business Incubator, West Java, Indonesia) - Hartati, Sri; ., Rendra Chaerudin; ., Lenny Martini (Journal of Education and Vocational Research, 2014)
The increasing number of unemployment and poverty led to increasingly perceived importance of entrepreneurship. Development will go well if supported by business because the government is very limited capabilities. Therefore, an entrepreneur development is potential both in number and quality. The fact is that the number of entrepreneurs facing Indonesia is still small and the quality was still low, so that entrepreneurship development is an urgent issue for the success of development. Therefore, model of entrepreneurship learning for new entrepreneur growth is very necessary. This study aims to obtain a model of entrepreneurial learning in entrepreneurial business growth through the use of methods, techniques and learning aids, determination of material and the effect on the growth of entrepreneur business. The study was conducted by using descriptive research and verification research. Unit of analysis is the institution of education providers that have business incubator, both public and private training. The success of entrepreneurial learning process is carried out by taking into account various factors, namely:Iinstructor,Course to be delivered,Methode that use, techniques and tools that will be used and the feedback is expected to learning process.The criteria used for the selection of prospective entrepreneurs consists of three criteria such as:motivation, entrepreneurship skills and business skills.The results showed that the model of learning effective and efficient learning must be adapted to need entrepreneur business include instructors, materials, techniques and tools which is used. This will affect the success of the learning activities in developing or growing entrepreneurial business.